Micro-welding of aluminium alloy by superposition of pulsed Nd:YAG laser and continuous diode laser - Okamoto, Y.; Nakashiba, S.; Sakagawa, T.; Okada, A. (Автоматическая сварка, 2013)
The combination of a pulsed Nd:YAG laser and a continuous diode laser could perform the high-performance micro-welding of
aluminum alloy. A pulsed Nd:YAG laser was absorbed effectively from the beginning of laser scanning by pre-heating Nd:YAG
laser pulse with the superposition of continuous LD, and wide and deep weld bead could be obtained with better surface integrity.